THE IMPORTANCE OF EDUCATIONAL AND DIDACTIC GAMES IN THE DEVELOPMENT OF CREATIVE ABILITIES OF PRESCHOOL CHILDREN - Lazzat Quralbayeva; Uktam Farmonov (Bright Mind Publishing, 2025)
This article explores the role and importance of educational-didactic games in developing the creative abilities of preschool children. Based on modern pedagogical approaches, it analyzes how these games influence imagination, thinking, communication skills, and problem-solving abilities. The psychological impact of the play environment is also discussed as a factor that fosters creativity in early childhood.
Keywords: Didactic games, preschool education, creative thinking, psychological development, modern pedagogy, Vygotsky, STEAM.